Les images auto-empruntées dans Les Vacances du cinéaste (Pays-Bas, Johan van der Keuken, 38 min., 1974) - Caroline Lardy (Mise au Point)
In the Film-maker’s Holiday, Johan van der Keuken repeatedly uses cinematic self-quotation. In doing so, he delivers a variation of the filmed diary that has been little explored until now. Numerous ill-assorted sources punctuate his narrative and create innovative effects of visual and sound assonance and dissonance by a subtle interplay of inclusion and exclusion. This article will attempt to put into perspective the methods of integrating the various elements and will examine the particular reappropriation engaged in by the film-maker.